Anatomical suitability and off-label use of contemporary transcatheter heart valves. (1st March 2022) - Werner, Nicolas; Renker, Matthias; Dörr, Oliver; Bauer, Timm; Nef, Holger; Choi, Yeong-Hoon; Hamm, Christian W.; Zahn, Ralf; Kim, Won-Keun
Abstract: Background: Despite excellent procedural results in a broad clinical population, certain anatomical or clinical conditions are still challenging for transcatheter aortic valve replacement (TAVI). Whether the adherence to the instructions for use (IFU) or the use of a clinically suitable device is a prerequisite for procedural success has not been well characterized. Aims: The anatomical and clinical suitability of new-generation transcatheter heart valves (THV) was evaluated in an all-comers population ( n = 540) at a high-volume center. Methods: Conformity with anatomical IFU criteria was evaluated in each implanted THV. In addition, the suitability of the implanted THV was verified in each case according to clinical and anatomical criteria, which had been previously defined according to the results of an international survey including 20 renowned TAVI operators. Furthermore, criteria of clinical suitability and adherence to IFU of each THV were applied to the overall cohort to analyze the proportion of patients in whom the use of the respective THV would have been judged to be unsuitable or off-label. Results: An off-label use of THV based on anatomical considerations was found in 20% of all procedures, whereas the implantation of a THV deemed to be clinically unsuitable was noted in 16.3% of all procedures. Clinical suitability and conformity with IFU were present to a varying extent across the THV systems. Neither clinical suitability, nor conformity with IFU were associated with device failure or periprocedural mortality. On multivariable analysis, aortic tortuosity, mean transaortic gradient and ascending aorta diameter were identified as independent predictors of device failure (VARC-3). Conclusions: Off-label TAVI and the use of clinically unsuitable THVs were common, but did not affect procedural outcomes. The variety of clinical and anatomical coverage of the different THV systems emphasizes the importance of an individualized THV selection. Highlights: The majority of anatomical and clinical conditions in a contemporary TAVI population can be treated properly with new-generation THVs. Vast differences exist in the anatomical coverage and clinical eligibility among all four THVs examined. An off-label or clinically unsuitable THV use was common in this all-comers TAVI population. Off-label use and the use of a "clinically unsuitable" THV were not associated with device failure after transfemoral TAVI.